العنونة في شعر فاديا غيبور ( للمرأة لغة أخرى ) أنموذجاً - حلوم أحلام بدر; صارم أمل محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
اتجهت الدراسات النقدية الحديثة، الغربية والعربية مؤخراً، إلى تسليط الضوء على العنوان، بوصفه نصاً، ومناصاً، يتموقع في واجهة النص، ليدل عليه، ويعرف به، ليشكل عتبات تفاوض القارئ، للانطلاق نحو فضاءات النص، وكشف أسراره، والتي يسعى العنوان إلى تمويهها، أو كشفها، أو إخفائها، في مراوغة وغواية. والعنونة عند فاديا غيبور تسحب القارئ بثقة إلى عوالم المرأة، ولغتها الأخرى، في بواكير دوواينها الشعرية ( للمرأة لغة أخرى )، بعنوان أنثوي يخفي أكثر ممّا يشفّ، تاركاً القارئ في حيرة السؤال، يقف على تخوم المعنى، ويبقى السؤال ماهي هذه اللغة الأخرى؟ ولماذا هي للمرأة دون الرجل ؟ The new critical studies, western and Arabic , have headed recently towards focusing on the title as a text and a paratext, placed at the front of the text to refer to and define it, which forms entrances that negotiate the reader to move towards the horizons of the text and reveal its secrets the title aims at concealing , revealing or hiding , using disguise and indirection. Entitling in Ghaibour’s poetry draws the reader confidently to the women’s worlds and her other language in her early divan " the women has another language ", with a feminine title hiding more than showing , leaving the reader puzzled, inquiring about meaning and asking : what is this other language ? And why is it exclusive for the women?